2005
DOI: 10.1111/j.1365-2125.2005.02516.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CYP2C8 polymorphism and grapefruit juice on the pharmacokinetics of repaglinide

Abstract: AimsThe primary aim of the study was to investigate the possible effect of the CYP2C8 * 3 allele and of grapefruit juice on the pharmacokinetics of repaglinide. Furthermore, the impact of a single dose of grapefruit juice on the pharmacokinetics of repaglinide in relation to dose. MethodsThirty-six healthy male subjects, genotyped for CYP2C8 * 3 (11 genotyped as CYP2C8 * 1/ * 3 , one as CYP2C8 * 3 /* 3 and 24 as CYP2C8 * 1/ * 1 ), participated in a randomized, cross-over trial. In the two phases, the subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…It is noteworthy that the individual f m,CYP2C8 values of repaglinide and the extent of the interaction were greatest in the two carriers of the CYP2C8*3 allele. Although the number of subjects in the present study was too small to draw any definitive conclusions, this finding is consistent with previous studies in which CYP2C8*3 was associated with increased clearance of repaglinide (Niemi et al, 2003b(Niemi et al, , 2005 and argues against the lack of association reported in other studies (Bidstrup et al, 2006;Tomalik-Scharte et al, 2011). The estimated f t,OATP1B1 of repaglinide is also in line with previous pharmacogenetic studies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is noteworthy that the individual f m,CYP2C8 values of repaglinide and the extent of the interaction were greatest in the two carriers of the CYP2C8*3 allele. Although the number of subjects in the present study was too small to draw any definitive conclusions, this finding is consistent with previous studies in which CYP2C8*3 was associated with increased clearance of repaglinide (Niemi et al, 2003b(Niemi et al, , 2005 and argues against the lack of association reported in other studies (Bidstrup et al, 2006;Tomalik-Scharte et al, 2011). The estimated f t,OATP1B1 of repaglinide is also in line with previous pharmacogenetic studies.…”
Section: Discussionsupporting
confidence: 80%
“…The relative roles of CYP2C8 and CYP3A4 may be slightly different with higher 0.5-to 4-mg doses of repaglinide (Bidstrup et al, 2003(Bidstrup et al, , 2006Kajosaari et al, 2005a;Kalliokoski et al, 2008c). In any case, the consequences of CYP2C8 inhibition depend on the therapeutic index of the victim drug and the significance of CYP2C8 in its elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Of note also is the fact that the repaglinide dose tested in both studies was clearly subclinical. Bidstrup et al (2006) also evaluated the role of the CYP2C8*3 polymorphism in the pharmacokinetics of repaglinide; however, they administered the drug in a clinically relevant dose of 2 mg. In this evaluation, the AUC and the maximal concentration of repaglinide did not differ significantly between 24 wild-type individuals and 12 carriers of the variant allele, one of whom was homozygous.…”
Section: Discussionmentioning
confidence: 99%
“…Niemi et al (2003bNiemi et al ( , 2005 found decreased (by 45-48%) AUC values of repaglinide in heterozygous carriers of the CYP2C8*3 variant allele, suggesting that it is related to a higher metabolic activity of the enzyme. On the other hand, the study by Bidstrup et al (2006) yielded no relevant differences in repaglinide pharmacokinetics with respect to this polymorphism.…”
Section: Introductionmentioning
confidence: 95%
“…The formation of the main metabolite M2 and especially that of M4 is largely dependent on CYP2C8, whereas the less important M1 is mainly formed by CYP3A4 (Bidstrup et al, 2003;Kajosaari et al, 2005a,b). The plasma concentrations of repaglinide are considerably raised by inhibitors of CYP2C8 (Niemi et al, 2003;Kajosaari et al, 2005a;Bidstrup et al, 2006). Because of its sensitivity to CYP2C8 inhibition and its short half-life, repaglinide has been recommended as a probe drug for studying CYP2C8 activity (Huang et al, 2007).…”
mentioning
confidence: 99%